2013
DOI: 10.4084/mjhid.2013.011
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Brucellosis in Children: Relative Frequency of Pancytopenia

Abstract: Hematological complications in brucellosis are common. Pancytopenia, although mainly reported in adults has also been described in children with brucellosis. This investigation was conducted to estimate the relative frequency of pancytopenia in children with brucellosis. The current study was conducted in Al-Khafji joint operation hospital, Saudi Arabia. Sixty patients with brucellosis, were enrolled in the study. Complete blood count (CBC) and blood culture were performed for all cases. Bone marrow (BM) aspir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 17 publications
4
39
1
2
Order By: Relevance
“…Our results were not in line with a Turkish study (8) which reported mean age of the study population 8.4±6.4 years, 53.2% females and 46.8% males. Our study found that 15.8 reported a history of ingestion of raw milk and dairy product and only 1.8% of them reported a history of animal contact, which was less than the El-Koumi MA et al study in Saudi Arabia (9) which found (83%) of the cases ingested raw animal milk and (45%) had a positive family history of brucellosis. This agreed with findings of Briones Lara et al (10) which reported 61 % of cases had consumed potentially infected milk or dairy products.…”
Section: Discussioncontrasting
confidence: 76%
“…Our results were not in line with a Turkish study (8) which reported mean age of the study population 8.4±6.4 years, 53.2% females and 46.8% males. Our study found that 15.8 reported a history of ingestion of raw milk and dairy product and only 1.8% of them reported a history of animal contact, which was less than the El-Koumi MA et al study in Saudi Arabia (9) which found (83%) of the cases ingested raw animal milk and (45%) had a positive family history of brucellosis. This agreed with findings of Briones Lara et al (10) which reported 61 % of cases had consumed potentially infected milk or dairy products.…”
Section: Discussioncontrasting
confidence: 76%
“…Roushan et al [18] reported anemia in 15.1%, leukocytosis in 12.2%, leukopenia in 3%, and thrombocytopenia in 3.4% of 469 patients. Pancytopenia has been found in 0.9%-21% of patients in different studies [2,[32][33][34][35]. There are conflicting data about the frequency of pancytopenia in different subgroups of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…There are four important species that may cause infection in humans, whereas B. melitensis is considered as the most invasive producing the most severe disease in humans (Godfroid et al 2005;El-Koumi et al 2013). B. melitensis is associated with small ruminants, although B. abortus may occasionally cause infection in sheep and goats.…”
Section: The Pathogenmentioning
confidence: 99%
“…The patient may show fever, chills, headache, muscle and joint pains, malaise, nausea, night sweats and lack of appetite for 3-6 weeks. The condition may also show a variety of non-specific haematological changes, such as anaemia and leucopenia (Plommet et al 1998;El-Koumi et al 2013).…”
Section: Disease In Humansmentioning
confidence: 99%
See 1 more Smart Citation